Let's solve the equation step by step:
-
Start with the equation:
\(-4b + 14 = 10\) -
Subtract 14 from both sides:
\(-4b + 14 - 14 = 10 - 14\)
This simplifies to:
\(-4b = -4\) -
Fill in the blanks:
- The missing term is:
-4
- The missing term is:
-
Divide both sides by -4:
\(-4b / -4 = -4 / -4\)
This simplifies to:
\(b = 1\)
In conclusion, we have:
- The completed process is:
- \( -4b + 14 = 10 \)
- \( -4b = -4 \)
- Subtract 14 from both sides
- \( b = 1 \)
- Divide both sides by -4
So, the final answers are:
- \( b = 1 \)
- The missing description is "Subtract 14 from both sides."
- The last operation involves "Divide both sides by -4."